PERAN PUBLIC RELATIONS DALAM KOMUNIKASI ORGANISASI DI PERPUSTAKAAN - Fepi Febianti (Maktabatuna, 2020)
Organizations cannot be separated from the process of interaction. This interaction cannot be limited in scope which is only limited to communication that occurs within the organization. Because in reality the pattern of interactions that occur within the organization ultimately addressed to the public outside the organization concerned. Organizations, be they small, medium or large, basically will always need a touch of active communication to foster public participation in the development of company operations All communication activities carried out by the organization are the tasks of the public relations department, although it is possible that in practice the public relations will coordinate and cooperate with other parts of the organization to carry out communication activities to achieve the stated goals.